Educating women: Schooling and identity in England and France 1800-1867 - Bellaigue, Christina De (Oxford Oxford University Press, 2007)
In the first part of the nineteeth century, an increasing number of middle class families were taking the education of their daughters seriously, and boarding-schools were multiplying on both sides of the Channel. Schoolmistresses - rarely, in fact, the 'reduced gentlewomen' of nineteenth century fiction - were not only often successful entrepreneurs, but also played an important part in the development of the teaching profession, and in the expansion of secondary education.